PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POWERPOINT PADA MATA PELAJARAN IPA KELAS IVC SD NEGERI 147 PEKANBARU - Sari Permanda; Mahmud Alpusari; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstact: this research is research and development aims to: (1) provide produce like learning media based on subject which worth to activity student learning in class IVC SD Negeri 147 Pekanbaru, (2) describe feasibility media. The model used is the development of Sugiyono Model only up on stage product trials. Data collection instruments the form of a questionnaire sheet media experts and matter experts, a questionnaire sheet product trials, and question pretest and postest. Learning media declared eligible by the feasibility test by: (1) Media experts by category Very Valid (3,6), (2) Matter experts by category Valid (3,33), (3) Product trials by category excellent (4,33). Based N-Gain, can be known improving student in class IVC SD Negeri 147 Pekanbaru that is 0,60 in the medium category. From the test result it can be concluded that learning media development based Powerpoint decent and effective used for Science subject in class IVC.Keyword: learning media based on Powerpoint, Science subject